2011
DOI: 10.1016/j.bmc.2011.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the activity of histone acetyltransferases by long chain alkylidenemalonates (LoCAMs)

Abstract: A novel class of KAT modulators (long chain alkylidenemalonates, LoCAMs) has been identified. Variations of the alkyl chain length can change the activity profile from inhibition of both KAT3A/KAT2B (as derivative 2a) to the peculiar profile of pentadecylidenemalonate 1b, the first activator/inhibitor of histone acetyltransferases. Together with the powerful apoptotic effect (particularly notable if considering that anacardic acid and other KAT inhibitors are not cell permeable) appoint them as valuable biolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 77 publications
(92 reference statements)
0
21
0
Order By: Relevance
“…Efforts to isolate small-molecule activators using the basic backbone structure of anacardic acid are currently underway. In a recent study, pentadecylidenemalonate was prepared, which surprisingly showed mixed inhibitor/ activator properties towards HATs, as this chemical inhibited p300/CBP HAT activity and activated PCAF HAT activity [74,75]. Pentadecylidenemalonate/SPV106 could cross mammalian cell membranes and enhance histone H3 acetylation.…”
Section: Druggability Of Hat Domainsmentioning
confidence: 99%
“…Efforts to isolate small-molecule activators using the basic backbone structure of anacardic acid are currently underway. In a recent study, pentadecylidenemalonate was prepared, which surprisingly showed mixed inhibitor/ activator properties towards HATs, as this chemical inhibited p300/CBP HAT activity and activated PCAF HAT activity [74,75]. Pentadecylidenemalonate/SPV106 could cross mammalian cell membranes and enhance histone H3 acetylation.…”
Section: Druggability Of Hat Domainsmentioning
confidence: 99%
“…Under chemically controlled conditions, these cells could be epigenetically reprogrammed to obtain functionally competent cardiovascular precursors with electrophysiology, gene expression, and microRNA profile similar to that of cardiomyocyte progenitors (11). Noteworthy, during the progress of these studies, we found that CMSC obtained from diabetic patients (D-CMSC) had a lower proliferation rate and failed to reprogram, suggesting the presence of a functional impairment (11,12).…”
mentioning
confidence: 98%
“…The proacetylation compound SPV106 has been described as an activator of the GCN5A/PCAF members of the GNAT family (20) and able to promote histone and nonhistone proteins acetylation (12). In our experiments, D-CMSC were cultured for ;6-8 days in the presence or absence of SPV106 at 25 mmol/L, a concentration established in a prior work (21).…”
Section: Epigenetic Enzymes Are Differentially Expressed Between Nd-cmentioning
confidence: 99%
“…11 However, besides being an expensive reagent, DMP is potentially explosive 12 and therefore not suitable for multigram scale. On the other hand, among the various oxidants for alcohols , the oxidation with with 2,2,6,6-tetramethylpiperidine-N-oxy (TEMPO) results very appealing since it is a non-metallic catalyst and, foremost, it is environmentally friendly and economical.…”
Section: Resultsmentioning
confidence: 99%